Deformation Differences in Complex Structural Areas in the Southern Sichuan Basin and Its Influence on Shale Gas Preservation: A Case Study of Changning and Luzhou Areas - He, Shun; Qin, Qirong; Li, Hu; Wang, Shilin (Frontiers in Earth Science, 2022)
Preservation conditions are the key factors that determine the effective accumulation of shale gas, The damage of faults formed by differential structures to the roof and floor and the shielding of lateral edges are the direct reasons for the difference of preservation conditions. Taking the organic rich shale of Wufeng-Longmaxi Formation in the south of Sichuan Basin as example, this paper reveals different types of shale gas rich structures by using typical seismic profiles, and puts forward the main controlling factors of different gas rich structures and their influence on preservation. The results show that three kinds of gas rich structures are developed in Wufeng-Longmaxi Formation in southern Sichuan: positive type, negative type and fault transformed slope type. The basin is dominated by wide and gentle syncline, fault spreading fold and low scope concealed anticlines. Wide and gentle anticline, arc anticline and fault transformation slope are developed at the basin edge. Fault sealing is the main controlling factor for the preservation of shale gas in wide and gentle anticlines. The main controlling factors for the preservation of circular arc anticlines and hidden anticlines are anticline curvature and the distance between faults. The preservation of shale gas in syncline is mainly controlled because it includes Formation buried depth, foliation development degree and Formation dip angle. The preservation of fault transformed syncline is mainly affected by Formation buried depth, dip angle and fault sealing, Foliation and faults form a three-dimensional migration system, which jointly controls the intensity of gas escape. Positive structures such as wide and gentle anticline and circular arc anticline at the basin edge, and deep buried gentle syncline and low scope concealed anticline in the basin are favorable shale gas rich structures.